Improving performance of additive manufactured (3D printed) concrete: A review on material mix design, processing, interlayer bonding, and reinforcing methods. (February 2021) - Kristombu Baduge, Shanaka; Navaratnam, Satheeskumar; Abu-Zidan, Yousef; McCormack, Tom; Nguyen, Kate; Mendis, Priyan; Zhang, Guomin; Aye, Lu
Abstract: The application of additively manufactured, 3D printed concrete in the construction industry has been gaining attention in recent years. 3D concrete printing (3DCP) has potentials for mass customisation, and off-site and rapid manufacturing of complex structural and architectural components. However, 3DCP has many challenges such as competing rheological requirements, weak interlayer bonding, difficulty in integrating reinforcement, and anisotropic material behaviour. Therefore, material properties of printed concrete are often inferior to traditional mould cast and leading to poor structural performance. Thus, satisfying performance criteria for structural applications is the key challenge of 3DCP, methods for enhancing the material properties of 3DCP are required. This article reviewed the main parameters affecting the performance of 3D printed concrete and discussed potential methods to enhance these properties. Methods investigated in this article include novel reinforcement, material modification, rheology control, nozzle design, process improvements, and interlayer bonding. Lastly, this article discussed the performance of structural elements produced by 3DCP and proposed future research areas to advance this technology in the building industry.